Cell fate decisions within the vascular cambium: initiating wood and bast formation - Haas, Aylin S.; Shi, Dongbo; Greb, Thomas (Frontiers in plant science, 2022)
Precise coordination of cell fate decisions is a hallmark of multicellular organisms. Especially in tissues with non-stereotypic anatomies, dynamic communication between developing cells is vital for ensuring functional tissue organization. Radial plant growth is driven by a plant stem cell niche known as vascular cambium, usually strictly producing secondary xylem (wood) inward and secondary phloem (bast) outward, two important structures serving as much-needed CO2 depositories and building materials. Because of its bidirectional nature and its developmental plasticity, the vascular cambium serves as an instructive paradigm for investigating principles of tissue patterning. Although genes and hormones involved in xylem and phloem formation have been identified, we have a yet incomplete picture of the initial steps of cell fate transitions of stem cell daughters into xylem and phloem progenitors. In this mini-review perspective, we describe two possible scenarios of cell fate decisions based on the current knowledge about gene regulatory networks and how cellular environments are established. In addition, we point out further possible research directions.
Gesehen am 20.09.2022